2015
DOI: 10.1248/bpb.b15-00152
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Duloxetine as Micronuclei Inducer in an Acute and a Subchronic Assay in Mouse

Abstract: Duloxetine is a widely used antidepressant worldwide. In the present report, we evaluated its capacity to induce micronucleated polychromatic erythrocytes (MNPEs) and micronucleated normochromatic erythrocytes (MNNEs) in mice. Two assays were performed, one with a single chemical administration and the other with daily chemical administration. In the first, we administered the antidepressant once to groups of 5 mice by the intragastric (i.g.) route (2, 20, and 200 mg/kg) and performed the analysis at 24, 48, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…Furthermore, in mouse bone marrow it was also reported that fluoxetine induced a duplication of SCE in comparison with the control level, no alteration in the cellular proliferation kinetics, and a weak decrease of the mitotic index with the highest tested dose. 25) Our present results demonstrated a genotoxic capacity of duloxetine which corresponded to an increase of about 58% over the control value with the three tested doses, an effect that although lower, agrees with a previous report that examined the drug as a micronuclei inducer, 9) as well as with a study in progress to determine the kinetics of DNA damage with the comet assay in liver and brain cells. The absence of dose response in the present assay could be in line with a strong genotoxic effect of the drug which starts from the first dose; this was shown with the calculation of the total genotoxic efficiency in our previous assay which used the same doses (2, 20, and 200 mg/kg), calculation which also suggested a decrease in the relative efficiency with respect to each of the applied doses, besides a dose-saturation effect.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Furthermore, in mouse bone marrow it was also reported that fluoxetine induced a duplication of SCE in comparison with the control level, no alteration in the cellular proliferation kinetics, and a weak decrease of the mitotic index with the highest tested dose. 25) Our present results demonstrated a genotoxic capacity of duloxetine which corresponded to an increase of about 58% over the control value with the three tested doses, an effect that although lower, agrees with a previous report that examined the drug as a micronuclei inducer, 9) as well as with a study in progress to determine the kinetics of DNA damage with the comet assay in liver and brain cells. The absence of dose response in the present assay could be in line with a strong genotoxic effect of the drug which starts from the first dose; this was shown with the calculation of the total genotoxic efficiency in our previous assay which used the same doses (2, 20, and 200 mg/kg), calculation which also suggested a decrease in the relative efficiency with respect to each of the applied doses, besides a dose-saturation effect.…”
Section: Discussionsupporting
confidence: 92%
“…Since the drug's approval in the first years of the present century its use has been substantially increased as shown by the account of about 42% of the antidepressant sales in 2012, and a major share of about 11 billion dollar/year. 14,15) However, organic collateral damage has been occasionally reported as well as moderate to severe withdrawal syndrome and the induction of DNA disturbances 9,16,17) ; moreover, the medicament can be used for weeks or months, a characteristic which suggests the pertinence of carrying out further toxicity tests that may be useful for the safety recommendations on its consumption. In this context, SCE has become a useful cytogenetic biomarker after the discovery that incorporation of the DNA base analog BrdU in combination with Höechst dye staining produced clear chromatid differentiation and revealed SCE.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, other assays have been performed. Antidepressants such as Duloxetine (a potent inhibitor of serotonin and noradrenaline reuptake), Imipramine and Desipramine (tricyclic antidepressants) have had their genotoxic capacity previously demonstrated in in vivo assays in a mouse [28][29][30] . The clastogenic, mutagenic and cytotoxic effects of trazodone (serotonergic antidepressant) and milnacipran (inhibitor of serotonin and noradrenaline reuptake) were investigated by using chromosomal aberrations (CAs), sister chromatid exchanges (SCEs), micronuclei (MN), and comet assays in cultured human peripheral lymphocytes 31 .…”
Section: Micronucleus Assaymentioning
confidence: 99%